Histological typing of intestinal tumours - Jass, Jeremy R; Sobin, L. H (Springer, 1989)
This second edition of the highly successful WHO histological classification of intestinal tumours is the result of an international collaborative effort by pathologists from nine countries. Revision was undertaken where necessary to reflect important changes that have occurred since the first edition in 1976. A bridge between the purely morphological and the immunological classification of the lymphomas is given. The approach to endocrine tumours, based on a combination of routine stains and immunohistochemical methods, supplants the former criteria based on silver stains. Considerable attention is given to the dysplasias, whose relevance in diagnostic pathology has increased with the advent of endoscopy. Several new entities have been added, and the precision of the proven sections has been enhanced. These changes update the classification, which will continue to facilitate data comparison by providing a standardized, international terminology.
International histological classification of tumours
Keywords: Neoplasms by Histologic Type; gastroenterologie; nádory podle histologického typu; Intestinal Neoplasms; střevní nádory; onkologie